2017
DOI: 10.18632/oncotarget.22164
|View full text |Cite
|
Sign up to set email alerts
|

CTHRC1 activates pro-tumorigenic signaling pathways in hepatocellular carcinoma

Abstract: CTHRC1 expression is involved in invasion and metastasis in various tumors. However, the molecules involved in its signaling pathways in hepatocellular carcinoma (HCC) remain elusive. The migration and invasion abilities of HCC cells stably expressing CTHRC1 were assessed in vitro and in vivo with a mouse model. Moreover, signaling pathways involved in invasion and metastasis were analyzed. CTHRC1 was abundantly expressed in HCC cell lines and HCC tissues. CTHRC1 was also detectable in the serum of HCC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Typically, it has been reported that the Akt signaling cascade and its up-and downstream molecules including EGFR, ERK1, PI3K, and MMP, etc. can also be modulated by CTHRC1 [24,32]. PI3K/Akt signaling has been shown to have a pivotal role in the proliferation, migration, invasion and EMT in the malignant progression of multiple tumors [33], and the importance of PI3K/Akt signaling in BCa development has been implicated [34].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it has been reported that the Akt signaling cascade and its up-and downstream molecules including EGFR, ERK1, PI3K, and MMP, etc. can also be modulated by CTHRC1 [24,32]. PI3K/Akt signaling has been shown to have a pivotal role in the proliferation, migration, invasion and EMT in the malignant progression of multiple tumors [33], and the importance of PI3K/Akt signaling in BCa development has been implicated [34].…”
Section: Discussionmentioning
confidence: 99%
“…CTHRC1 promotes invasiveness and metastasis of hepatocellular carcinoma through the activation of PI3K/protein kinase B (PKB)/AKT/ERK/cAMP response element-binding protein (CREB) signaling pathway, which induces EMT change and MMP2/MMP9 expression [ 128 ]. CTHRC1 is highly expressed in hepatitis B virus- (HBV-) associated hepatocellular carcinoma.…”
Section: Signaling Pathways Mediated By Cthrc1 Involved In the Promentioning
confidence: 99%
“…As mentioned above, CTHRC1 in hepatocellular carcinoma can induce HIF-1 α to promote tumor angiogenesis and regulate downstream MMPs and tumor suppressor gene p53 by activating the PI3K/AKT signaling pathway [ 128 ]. In human squamous cell carcinoma, HIF-1 α overexpression stimulates VEGF-C upregulation and induces lymphangiogenesis and tumor cell invasion [ 131 ].…”
Section: Signaling Pathways Mediated By Cthrc1 Involved In the Promentioning
confidence: 99%
“…Our research suggests that PLEK2 and SCN7A may be used as potential biological markers for the early diagnosis of NSCLC. [20,21], MMP12 [22], UBE2T [23], ECT2 [24,25], SULF1 [26], HMGB3 [27], and CTHRC1 [28,29]. Besides, we identified PLEK2 and SCN7A as potential biomarkers of NSCLC.…”
Section: Discussionmentioning
confidence: 99%